Ecological approaches to rural development projects - Sandra Díaz; Daniel M. Cáceres
Most rural development projects include ecological considerations, and most conservation projects include some reference to sustainable development. However, conservation projects frequently fail because they do not incorporate local communities' perceptions and needs. Many development projects are also unsuccessful because they are not based on adequate ecological assessment. We focus here on the most important ecological issues to be addressed in order to place development projects in an ecosystem context. Such projects should incorporate updated and precise ecological concepts and methods. Some key ecological issues in development projects are the relationships between ecosystem functions, services, and sustainability, the concept of loose connectivity, the distinct and complementary concepts of ecosystem resistance and resilience, and the links between biodiversity and ecosystem functioning. We claim that an ecologically sound development project maximizes the preservation and improvement of ecosystem services, especially for local communities. We pose a series of questions aimed at placing rural development projects in an ecosystem context and suggest ways of organizing this information.